The Cranberries - The Cranberries; Fairbairn, Bruce; Island Records (United Kingdom : Island Records, 1996)
Contains two versions of the single.
CD 1 : When You're Gone (edit) -- When You're Gone (LP version).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rock music